THE INFLUENCE OF LEISURE TOURISM ON THE WELL-BEING OF CITIZENS OF UZBEKISTAN (Web of Teachers: Inderscience Research, 2024)
In this research psychological, social and economic effect of the contribution of leisure tourism among the concerned citizen well-being of Uzbekistan in analyzed. Through secondary research of academia and government sources of information including statistics on tourism, it is proven that tourism highly contributes in the reduction of stress and in the promotion of mental health. Tourism provides as economic support its supporting local economies by creating jobs, investing in infrastructure and enhancing living standards. This is good because in social terms it encourages cultural exposure, brings community pride and makes people involved with their culture of heritance. As tourists grow and exceed capacity, the research also highlights challenges, like cultural commercialization and intercommunity social tension, that may arise. This study highlights that issues of such importance as sustainable tourism practice are important for a positive influence on tourism and preservation of environment, as well as of culture. Our results reveal that the tourists not only gain, but the whole community also reaps the long-term benefits during the process of tourism development.Tourism, according to different experts and researchers identified is one of the fastest developing industries within the globe and presently one of the prominent components of the tourism industry. In expansion experts believe that for a better understanding of cultural tourism, it is crucial to know how the world heritage sites fulfill visitors' needs. Along with this, experts are too concerned about the massive intrusion and tourist industrial development, which brings numerous social changes in a particular community (Abbasi Dorcheh & Mohamed, 2013). In order to develop the tourism industry in a particular region. Sustainability needs to be the core indicator.The idea about sustainability in the tourism industry is basically, adopted from sustainable development. Therefore, many organizations and experts defined sustainability in their own ways. Such as, World Tourism Organization (WTO, 1993) defines sustainable tourism as "Tourism that takes full account of its current and future economic, social and environmental impacts, addressing the needs of visitors, the industry, and the environment and host communities". Sustainability is the main key, in tourism development. Therefore, the World Health Organization emphasizes sustainable tourism development strategies and management practices that are suitable to all forms of tourism in all types of destinations. In addition, socio-cultural, economic, and environmental tourism development is the utmost significant dimension of sustainable development (WTO, 2013).